Adipose tissue depot differences in adipokines and effects on skeletal and cardiac muscle. (June 2020) - Rodríguez, Amaia; Becerril, Sara; Hernández-Pardos, Ana Wenting; Frühbeck, Gema
Abstract : White (WAT) and brown (BAT) adipose tissue communicate with skeletal muscle and heart through the secretion of adipokines (adiponectin, leptin, omentin, osteopontin or cardiotrophin-1) and batokines (BMP8b, FGF-21, endothelin-1 or IL-6), respectively. Furthermore, several bioactive lipids termed lipokines [palmitoleate (C16:1n7) or 12, 13-diHOME] and microRNAs capsuled in exosomes (miR-27a, miR122, miR-130b, miR-155, miR-200a or miR-320d) secreted from white and brown adipocytes also influence the skeletal and cardiac muscle function. The review focuses on the depot-related differences in adipose tissue-derived signals (adipokines, batokines, lipokines and exosomal miRNAs) and their impact on skeletal muscle under physiological conditions as well as in obesity. The relevance of regular physical activity and exercise on fat depot-specific adaptations to improve metabolic health will also be addressed.